Chemical-recognition-driven selectivity of SnO2-nanowire-based gas sensors - Park, Hyoungwon; Kim, Jae-Hun; Vivod, Dustin; Kim, Sungil; Mirzaei, Ali; Zahn, Dirk; Park, Changkyoo; Halik, Marcus; Kim, Sang Sub (Nano Today, 2021)
The sensing capabilities of semiconducting metal oxide (SMO)-based gas sensors, which are a promising type of sensors, were improved in the present study using a novel method that enhanced gas selectivity toward various gas molecules. A simple and effective post-modification with functional self-assembled monolayer (SAM) molecules enhanced the selective sensing properties. The chemical-affinity-driven interaction between SAM and gas molecules enabled selective gas sensing, and the small size of SnO2 nanowires (NWs; diameter = 50 nm) provided a large sensing area. Moreover, simple alteration of the chemical moiety in SAM molecules facilitated the tuning of SAM-induced selectivity over a broad range of collections. The binding of SAMs on the NWs was analyzed by infrared spectroscopy, thermogravimetric analysis, and X-ray photoelectron spectroscopy, with the selective gas sensing being investigated under various sensing conditions. The results from the molecular dynamics simulations supported the proposed selective sensing mechanism. The combination of passivation and selective gas sensing resulted in a simple method for the selective gas sensing of SnO2 NWs, and the concept could be generally expanded to other types of SMO-based sensing platform
Keywords: Self-assembled monolayer; SnO2 nanowire; Gas sensor; Selectivity; Surface chemistry; MD simulation

Reversible chirality inversion of an AuAgx-cysteine coordination polymer by pH change - Ni, Bing; Vivod, Dustin; Avaro, Jonathan; Qi, Haoyuan; Zahn, Dirk; Wang, Xun; Cölfen, Helmut (Nature Communications, 2024)
Responsive chiral systems have attracted considerable attention, given their potential for diverse applications in biology, optoelectronics, photonics, and related fields. Here we show the reversible chirality inversion of an AuAgx-cysteine (AuAgx-cys) coordination polymer (CP) by pH changes. The polymer can be obtained by mixing HAuCl4 and AgNO3 with L-cysteine (or D-cysteine) in appropriate proportions in H2O (or other surfactant solutions). Circular dichroism (CD) spectrum is used to record the strong optical activity of the AuAg0.06-L-cys enantiomer (denoted as L0.06), which can be switched to that of the corresponding D0.06 enantiomer by alkalization (final dispersion pH > 13) and can be switched back after neutralization (final dispersion pH <8). Multiple structural changes at different pH values (≈9.6, ≈13) are observed through UV-Vis and CD spectral measurements, as well as other controlled experiments. Exploration of the CP synthesis kinetics suggests that the covalent bond formation is rapid and then the conformation of the CP materials would continuously evolve. The reaction stoichiometry investigation shows that the formation of CP materials with chirality inversion behavior requires the balancing between different coordination and polymerization processes. This study provides insights into the potential of inorganic stereochemistry in developing promising functional materials.
CRIS-Team Scopus Importer:2024-03-22

Superoleophilic Magnetic Iron Oxide Nanoparticles for Effective Hydrocarbon Removal from Water - Sarcletti, Marco; Vivod, Dustin; Luchs, Tobias; Rejek, Tobias; Portilla Berlanga, Luis; Müller, Lukas; Dietrich, Hanno; Hirsch, Andreas; Zahn, Dirk; Halik, Marcus (Advanced Functional Materials, 2019)
Various hydrocarbons are efficiently extracted from water by using a new sorbent material based on covalently functionalized magnetic nanoparticles. The functionalization of the magnetite nanoparticles with a self‐assembled monolayer of hexadecylphosphonic acid renders the nanoparticles oleophilic and the magnetic nature of magnetite allows for simple extraction of the hydrocarbon‐soaked sorbent. The sorbent material is capable of extracting single contaminants such as alkanes and aromatics and complex hydrocarbon mixtures such as crude oils in high extraction rates of up to 14 times the sorbent volume. Experimental results are explained by molecular dynamics simulations on the adsorption of single components from a hydrocarbon‐water mixture to the alkylphosphonic acid layer on the nanoparticles. The core–shell sorbent material is highly stable and therefore, reusable over several successive extraction cycles without degradation. The extraction performance is determined at different water temperatures, different water sources, and different magnetic core materials and evaluated compared to heptadecanoic acid functionalized magnetite. The new sorbent material provides the opportunity for an efficient, reliable, inexpensive, and environmental friendly removal of hydrocarbons from wate
Keywords: magnetic nanoparticles; functionalized nanoparticles; oil extraction; water remediation; phosphonic acids

Tailored solution‐based N‐heterotriangulene thin films: Unravelling the self‐assembly - Hawly, Tim; Streller, Fabian; Johnson, Manuel; Miguez Lago, Sandra; Hammer, Natalie; Hampel, Frank; Vivod, Dustin; Zahn, Dirk; Kivala, Milan; Branscheid, Robert; Spiecker, Erdmann; Fink, Rainer (ChemPhysChem, 2021)
The ability of a series of bridged triarylamines, so‐called N‐heterotriangulenes, to form multilayer‐type 2D‐extended films via a solution‐based processing method was examined using complementary microscopic techniques. We found that the long‐range order, crystallinity, and layer thickness decisively depend on the nature of the substituents attached to the polycyclic backbone. Owing to their flat core unit, compounds exhibiting a carbonyl unit at the bridge position provide a superior building block as compared to thioketone‐bridged derivatives. In addition, nature and length of the peripheral substituents affect the orientation of the aromatic core unit within highly crystalline films. Hence, our results stress the significance of a suitable molecular framework and provide deeper understanding of structure formation in 2D‐confined surroundings for such compounds.<br
Keywords: bridged triarylamines; self-assembly; organic semiconductors; 2D nanomaterials; organic electronics

Tailoring the Wetting Behavior of Self-Assembled Monolayers by Surface Charge - Vivod, Dustin; Voß, Johannes; Halik, Marcus; Zahn, Dirk (Journal of Physical Chemistry C, 2024)
The wetting of (mixed) self-assembled monolayers (SAMs) is characterized as a function of surface charge. Using a combination of molecular dynamics simulations and contact angle measurements, we unravel the arrangement of dipoles and hydrogen bonds at the interface. Our basis simulation model features alkyl functionalization of an aluminum oxide surface via n-alkyl-phosphonic acid [C18H37-PO(OH)2] molecules, which represents a commonly used hydrophobic SAM surface readily accessible to contact angle measurements. We then probed the effect of charging the alkyl-terminated SAMs to unravel the interplay of local hydrophobicity and the overall dipole arrangement within the droplets. Strikingly, we find that moderate positive charging retains the hydrophobic character and potentially makes the SAMs even more hydrophobic than their uncharged counterpart. We attribute this phenomenon to the hindering of dangling hydrogen atoms at the water-alkyl contact, as a consequence of dipole rearrangements. While our simulation models predict a contact angle increase by 10° as an upper estimate for boosting hydrophobicity, experimental analyses of mixed SAMs using imidazole/alkyl-terminated species showed roughly constant wetting behavior for moderately positive charging.
CRIS-Team Scopus Importer:2024-05-24

The remediation of nano-/microplastics from water - Sarcletti, Marco; Park, Hyoungwon; Wirth, Janis; Englisch, Silvan; Eigen, Andreas; Drobek, Dominik; Vivod, Dustin; Friedrich, Bernhard; Tietze, Rainer; Alexiou, Christoph; Zahn, Dirk; Apeleo Zubiri, Benjamin; et al. (Materials Today, 2021)
Nano-/microplastics (NP) is a human-made emerging contaminant with worldwide occurrence. The small size (below one micrometer), the different chemical nature and the persistence make NP to potential hazards with suspect probability of tissue penetration and inflammation or as accumulator for toxins. A strategy to stop the spill of novel NP is the remediation from waste water or rivers as prominent distributors. We have developed core–shell superparamagnetic iron oxide nanoparticles (SPIONs) that attract NP and glue them to larger agglomerates which then can be removed from water by applying an external magnetic field. The shell molecules provide two interaction motifs towards NP. The tuned surface potential of the functionalized SPIONs attract complementary charged NP efficiently and the n-alkyl chain is dedicated to preferential interaction towards organic NP rather than inorganic particles. Structural analytics and molecular dynamics simulation support the proposed concept. Systematic remediation experiments with different NP (chemical structures, sizes and mixtures), from different waters – including river water – and with different SPION core materials indicate a universal validity of the concept, with best remediation performance for mixed NP. We suggest a method for broadband remediation of various NP with simple materials and processes, which both have the potential to be up-scaled.<br

Use of oleophilic magnetite nanoparticles as efficient sorbent for water contaminants - Sarcletti, Marco; Vivod, Dustin; Luchs, Tobias; Rejek, Tobias; Portilla, Luis; Hirsch, Andreas; Zahn, Dirk; Halik, Marcus (ABSTRACTS OF PAPERS OF THE AMERICAN CHEMICAL SOCIETY, 2019)
CRIS-Team WoS Importer:2019-08-23